Predicting student’s pro-environmental behavior based on antecedent’s factors: A confirmatory study - Priadi, Agus; Apriyanti, Eka; Fatria, Erian (Universitas Negeri Jakarta, 2025)
Climate change disasters as a result of environmental degradation have become a threat to every component of the Earth's environment. These disasters are strongly suspected to be caused by harmful behaviors toward the environment, including among student groups. Therefore, efforts are needed to promote and empower pro-environmental behavior (PEB) in society. The purpose of this study is to provide information and confirm pro-environmental behavior (PEB) based on antecedent factors of environmental instructional leadership (EIL) and environmental personality traits (EPT), mediated by the New Environmental Paradigm (NEP). A quantitative research method with a causal study approach was carried out involving 47 Environmental Health students who selected using multistage random sampling. Four research instruments were used, consisting of statements adapted from previous research. Data analysis techniques employed were path analysis. The results confirmed that EIL had a direct effect on NEP and PEB, but the effect was not significant. Meanwhile, EPT had a very significant direct effect on NEP and PEB. The NEP variable was found to be a good mediator in bridging the influence of EIL and EPT on PEB. If pro-environmental behavior among students is to improve and its variability minimized, these antecedent factors can be empowered through environmental education and learning strategies, prioritizing NEP based on empirical findings.